2014
DOI: 10.1093/infdis/jit839
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus and Other Respiratory Viral Infections in Older Adults With Moderate to Severe Influenza-like Illness

Abstract: Background. Few studies have prospectively assessed viral etiologies of acute respiratory infections in community-based elderly individuals. We assessed viral respiratory pathogens in individuals ≥65 years with influenza-like illness (ILI).Methods. Multiplex reverse-transcriptase polymerase chain reaction identified viral pathogens in nasal/throat swabs from 556 episodes of moderate-to-severe ILI, defined as ILI with pneumonia, hospitalization, or maximum daily influenza symptom severity score (ISS) >2. Cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
217
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(232 citation statements)
references
References 23 publications
9
217
2
4
Order By: Relevance
“…Severe illness and death among laboratory-confirmed RSV-infected adults has been reported (29,30), even though the clinical association between pathogen detection and disease remains difficult to interpret in the absence of comparison groups (i.e., RSV prevalence among adults without respiratory illness). Studies conducted in Kenya and South Africa that compared the RSV prevalence among patients hospitalized with severe acute respiratory illness (SARI) to control groups found that RSV infection was associated with hospitalization among children <5 years of age, but no association was found among persons >5 years of age (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Severe illness and death among laboratory-confirmed RSV-infected adults has been reported (29,30), even though the clinical association between pathogen detection and disease remains difficult to interpret in the absence of comparison groups (i.e., RSV prevalence among adults without respiratory illness). Studies conducted in Kenya and South Africa that compared the RSV prevalence among patients hospitalized with severe acute respiratory illness (SARI) to control groups found that RSV infection was associated with hospitalization among children <5 years of age, but no association was found among persons >5 years of age (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Since hMPV, RSV, and HPIV-3 have been implicated in serious nosocomial outbreaks in adults, we placed patients with hMPV, RSV, or HPIV-3 on standard, contact, and droplet precautions for cough duration and used single rooms when available. [8][9][10] Early in the influenza epidemic here, influenza and ILI patients were given single rooms. Influenza patients had single room priority and cohorting was performed whenever possible.…”
Section: Infection Control Implications Of Protracted Lengths Of Staymentioning
confidence: 99%
“…Because some viral ILIs (eg, hMPV, RSV, HPIV-3) have potential for nosocomial spread and serious hospital outbreaks, we thought it prudent to put these ILI patients in single rooms. 9,10 Since the viral etiology of ILIs was known by PCR, it was thought that cohorting would decrease the bed burden, but cohorting was of limited value because ILIs of the same type were not in hospital at the same time. Single room availability was further limited by the prolonged LOS of some ILI viruses-for example, RSV (8.1 days) and R/E (8 days).…”
Section: Infection Control Implications Of Protracted Lengths Of Staymentioning
confidence: 99%
“…The ILI data compiled by the Centers for Disease Control and Prevention (CDC) on the basis of a sample of 2900 outpatient health care providers in all states, representing .30 million patient visits each year, show wide variation in the timing and strength of each (presumed) influenza season. ILI, defined as "fever (temperature of 100°F [37.8°C] or greater) and a cough and/or a sore throat without a known cause other than influenza," is a commonly encountered clinical entity (11)(12)(13)(14). Although the CDC data provide weekly estimates of the percentage of all outpatient visits caused by ILI at a national level, some studies (11)(12)(13)(14) suggest that considerably ,50%, perhaps as low as 20%, of such clinical syndromes may be caused by true influenza.…”
mentioning
confidence: 99%
“…ILI, defined as "fever (temperature of 100°F [37.8°C] or greater) and a cough and/or a sore throat without a known cause other than influenza," is a commonly encountered clinical entity (11)(12)(13)(14). Although the CDC data provide weekly estimates of the percentage of all outpatient visits caused by ILI at a national level, some studies (11)(12)(13)(14) suggest that considerably ,50%, perhaps as low as 20%, of such clinical syndromes may be caused by true influenza. ILI, therefore, probably reflects a set of clinical symptoms that can be caused by a large number of viruses infecting the upper and lower respiratory tracts, including rhinovirus, adenovirus, respiratory syncytial virus, parainfluenza virus, and human metapneumovirus.…”
mentioning
confidence: 99%